Dangerous Gifts Imperialism, Security, and Civil Wars in the Levant, 1798-1864 - Ozavci, Ozan (Oxford University Press, 2021)
From Napoleon Bonaparte's invasion of Egypt in 1798 to the foreign interventions in the ongoing civil wars in Syria, Yemen, and Libya today, global empires or the so-called Great Powers have long assumed the responsibility of bringing security to the Middle East. The past two centuries have witnessed their numerous military occupations to 'liberate', 'secure', and 'educate' local populations. Consulting fresh primary sources collected from some thirty archives in the Middle East, Russia, the United States, and Western Europe, Dangerous Gifts revisits the late eighteenth- and nineteenth-century origins of these imperial security practices. It questions how it all began. Why did Great Power interventions in the Ottoman Levant tend to result in further turmoil and civil wars? Why has the region been embroiled in a paradox-an ever-increasing demand for security despite the increasing supply-ever since? It embeds this highly pertinent genealogical history into an innovative and captivating narrative around the Eastern Question, freeing the latter from the monopoly of Great Power politics, and also foregrounding the experience and agency of the Levantine actors: the gradual yet still forceful opening up of the latter's economies to global free trade, the asymmetrical implementation of international law from their perspective, and the secondary importance attached to their threat perceptions in a world where political and economic decisions were ultimately made through the filter of global imperial interests.